Does persisting fear sustain catatonia?. (31st August 2017) - Fink, M.; Shorter, E.
Abstract : Objective: To examine the psychological substrate of catatonia. Method: Reviewing the historical descriptions and explanations of catatonic behaviours by clinicians from its delineation in the 19th century to the present. Results: Patients with catatonia are often haunted by fears and terrors; this has not been widely appreciated, and certainly was lost from view in the days when catatonia was considered a subtype of schizophrenia. The report contributes to resolving a major question in catatonia: is the mind in stupor inactive, as the blank state that we picture in anesthetized patients, or is the mind active, so preoccupied as to exclude all other influences. The main finding: Persistent fear occupies the mind of catatonic patients. Conclusion: The signs of catatonia are adaptations to persistent fear, akin to tonic immobilization. The relief afforded by sedation supports this interpretation.